Reaper of souls - Barron, Rena (Barron, Rena. Kingdom of souls, 2021)
Achieving long-coveted magic at a devastating price, Arrah returns to tribal lands to search for the remnants of her parents' people while struggling to decipher her mysterious connection to the Demon King.